Financial Revenues from Timber Harvesting in Secondary Cloud Forests: A Case Study from Mexico - Toledo-Aceves, T.; Günter, S.; Guariguata, Manuel R.; García-Díaz, M.; Zhunusova, E. (MDPI, 2022)
Secondary forests, i.e., those arising after the clearance and abandonment of previously forested land, dominate tropical forest landscapes, rapidly sequester carbon, provide essential ecosystem services and are prone to re-clearance. Secondary cloud forests (SCF) play a particularly critical role for biodiversity and hydrological regulation. To promote their persistence, sustainable management is necessary; however, there is limited information regarding SCF potential for sustainable timber production. We estimated the revenue from selective timber harvesting in a pilot study in a 20-year-old SCF in Mexico. We explored the effect of the harvested timber volume, harvesting costs and price of forest products on the Net Present Value (NPV). Small landowners could only extract 17% of the harvestable standing volume due to a high number of small trees, a high (34%) volume of non-timber species, and their limited capacity to process timber. A third of the income derived from fuelwood, and overall financial returns were negative. A positive NPV may result from a 20% harvesting intensity, a 10% reduction in harvesting costs, or a 20% increase in stumpage price. Our results warrant the development of forest policy instruments and economic incentives for small-scale SCF landowners to alleviate poverty and meet national and global restoration and climate mitigation goals.